(untitled) (Unilorin Journal of Lifelong Education, 2025)
The study examined the efficacy of Motivational Interviewing (MI) in reducing risky sexual behaviour among in-school adolescents in Lagos State, Nigeria. The study adopts a quasiexperimental pretest-posttest control group design to assess the impact of MI on adolescents' engagement in unprotected intercourse, multiple sexual partnerships, early sexual debut, and substance use during sexual encounters. The population comprises all in-school adolescents in Lagos State, while the target population consists of secondary school students. A multi-stage sampling technique was employed to select participants, resulting in a sample size of 140 adolescents. Data were collected using the Sexual Risk Survey (SRS) and a researcher-developed Risky Sexual Behaviour Questionnaire (RSBQ). The instruments were validated by experts, and reliability was established through a pilot study, yielding a Cronbach’s alpha of 0.88 and a testretest reliability coefficient of 0.93. Data were analyzed using Analysis of Covariance (ANCOVA) at a 0.05 significance level. Findings indicate that MI significantly reduces risky sexual behaviour among adolescents. The study further reveals no significant interaction between gender and MI, implying that both male and female adolescents benefit equally. However, a significant interaction between age and MI was observed, with older adolescents responding more positively due to cognitive maturity. Ethical considerations, including informed consent, confidentiality, and voluntary participation, were upheld. The study concludes that MI is an effective intervention and recommends its integration into school-based sexual health programs, ensuring gender-neutral training and age-specific adaptations to maximize impact. The findings contribute to evidencebased approaches in adolescent health interventions.